ASSOCIATION BETWEEN HEALTHCARE ACCREDITATION AND CARDIOPULMONARY RESUSCITATION OUTCOMES: A FISHBONE-BASED ANALYSIS OF IN-HOSPITAL CARDIAC ARREST - Kinawy, Sayed; Ahmed Hamed Mohamed Eldarsy; Shimaa Abdelfatah Abdelmuniem Mohamed; Abdulhakim Ahmed Assalahi; Radwa Mohamed Rashed; Amr Refat Elsafty; Dafer saleh AlBahri; Mustafa Fadlalla Mohamed Ali Fadlalla; Mohammed Hammed Alswaidan; Mohammed Abdullah Morshed; Nasser Hebah Thabit Almakrami; Mohammad Abdelrahman Hussein; Aldhili Mohammed Khalid (International Journal of Patient Safety and Quality, 2026)
Background:Cardiopulmonary resuscitation (CPR) outcomes for in-hospital cardiac arrest (IHCA) are critical indicators of hospital performance. This study assessed the impact of accreditation by the Central Board for Accreditation of Healthcare Institutions (CBAHI) on CPR outcomes at New Najran General Hospital in Saudi Arabia, using a fishbone analysis to identify contributing factors. Methods:As retrospective pre–post observational study was conducted on 251 adult ICU patients who experienced IHCA and received CPR between 2021 and 2022. Data were collected from hospital records, focusing on return of spontaneous circulation (ROSC) and survival to discharge (STD). A fishbone diagram was used to analyze potential factors influencing CPR outcomes. Results: ROSC was achieved in 69.4% of patients, and the STD rate improved from 2.3% in 2021 to 4.8% in 2022. Survival was significantly associated with younger age (P < 0.001), witnessed arrests (P = 0.017), and shockable rhythms (P < 0.001). Following accreditation, ACLS certification among staff rose from 60% to 95%, correlating with better outcomes. Gender, illness category, and mechanical ventilation showed no significant association on survival, However, adjusted analyses did not demonstrate a statistically significant independent association between accreditation-related variables and survival to discharge. Conclusion: The observed improvements in outcomes appear to be multifactorial, with accreditation serving as one contributing element alongside broader system-level and clinical care enhancements.